1993
DOI: 10.1055/s-2007-1013814
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Harvesting Techniques on the Arterial Wall of the Internal Mammary Artery Graft: Microscopic Analysis

Abstract: An histological comparison was made between left internal mammary arteries (LIMAs) harvested and prepared with different techniques prior to coronary artery bypass grafting. The mobilization of LIMA was made as follows: conventional technique (group I), extra pleural takedown with lysis of the endothoracic fascia (group II), and LIMA skeletonization (group III). Each group was divided into two other sub-groups according to the LIMA graft preparation: papaverine-saline solution sprayed on the pedicle (sub-group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 1 publication
0
8
1
Order By: Relevance
“…However, they showed 2 cases of microthrombi adherent to the endothelial layer [Gaudino 1999]. Noera and coworkers have not found any evidence of superior damage in the skeletonized group compared with a pedicled group [Noera 1993]. In our study, we have not found any damage to the endothelial layer such as intimal dissection, irregularity, or thrombus formation.…”
Section: E161contrasting
confidence: 53%
“…However, they showed 2 cases of microthrombi adherent to the endothelial layer [Gaudino 1999]. Noera and coworkers have not found any evidence of superior damage in the skeletonized group compared with a pedicled group [Noera 1993]. In our study, we have not found any damage to the endothelial layer such as intimal dissection, irregularity, or thrombus formation.…”
Section: E161contrasting
confidence: 53%
“…Both Deja and coworkers 16 and Wendler and coworkers 6 found skeletonized LIMAs to have higher free ûow compared with pedicled conduits, but we found LIMA flow was similar between two groups. Both studies measured ûows after intra-arterial papaverine injection, which has been demonstrated to cause endothelial damage to the mammary artery by Noera et al 17 Accordingly, we never used intraluminal papaverine on LIMA.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for choosing the skeletonized dissection of the internal thoracic artery is that it provides greater length 14,25,29,[32][33][34] and caliber 17 compared with those provided by the conventional technique (pedicled), and, therefore, may revascularize coronaries with distal lesions. In addition, it maintains the internal thoracic artery in its in situ form, which is advantageous, because a 10 to 15% loss in the patency of that vessel is known to occur when it remains as a free graft, being anastomosed in the ascending aorta 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The skeletonized dissection of the internal thoracic artery provides advantages, such as the preservation of the collateral circulation of the sternum, which reduces sternal complications [23][24][25]29,[31][32][33][34][35][36] and respiratory complications, due to pleural preservation 19,20 . In addition, the greater initial flow decreases the occurrence of hypoperfusion syndrome 16,17 , considering the longer time of dissection (10 to 15 min) 16 .…”
Section: Discussionmentioning
confidence: 99%